Value Added Analysis and Development Strategy of Spiced Tea Bags at PT Indo Spices Trading - Ahya, Ratu Maulida; Aziz Husyairi, Khoirul (IPB University, 2024)
PT Indo Spices Trading took advantage of the opportunity to create functional beverage products, namely spiced tea bags made from leftover export quality cardamom and ginger, plus other spices. Input transformation increases the output value of spiced tea bags due to costs, resulting in a new, higher price and increasing profits. Therefore, added value analysis is needed to determine the extent of added value and level of profitability obtained from processing spiced tea bags, as well as analyzing appropriate development strategies to increase it competitiveness and consumer acceptance in the market. The methods used include the Hayami method and SWOT analysis. The research results show an added value of IDR 138,142 per kilogram for spiced tea bags, with an added value ratio of 47%. The profit obtained from spiced tea bags is IDR 120,642 with a profit margin of 87%. Recommended strategic alternatives for developing spiced tea bags based on SWOT analysis are to utilize Strengths and Opportunities (S-O), namely: 1) increasing sales of spiced tea bags by prioritizing inherent product attributes, and 2) establishing partnerships with modern retail outlets